Reflection for higher order risk preferences - Han Bleichrodt; Paul van Bruggen (Tinbergen Institute, 2018)
Higher order risk preferences are important determinants of economic behaviour. We apply behavioural insights to this topic: we measure higher order risk preferences for pure gains and pure losses by controlling the reference point. We find a reflection effect not only for second order risk preferences, as in Kahneman and Tversky 1979, but also for higher order risk preferences: we find risk aversion, prudence and intemperance for gains, but risk loving preferences, imprudence and temperance for losses. The risk aversion and intemperance for gains and the imprudence for losses is evidence against a preference for combining good with bad or good with good, which previous theoretical and empirical results suggest may underlie higher order risk preferences.
Keywords: C91; D81; D91; 330; Risk Apportionment; Higher Order Risk Preferences; Risk Aversion; Prudence; Temperance; Reference Dependence